1991
DOI: 10.3758/bf03205036
|View full text |Cite
|
Sign up to set email alerts
|

The reduction of saccadic latency by prior offset of the fixation point: An analysis of the gap effect

Abstract: The latency to initiate a saccade (saccadic reaction time) to an eccentric target is reduced by extinguishing the fixation stimulus prior to the target onset. Various accounts have attributed this latency reduction (referred to as the gap effect) to facilitated sensory processing, oculomotor readiness, or attentional processes. Two experiments were performed to explore the relative contributions of these factors to the gap effect. Experiment 1 demonstrates that the reduction in saccadic reaction time (RT) prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

19
187
4
6

Year Published

1994
1994
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 301 publications
(216 citation statements)
references
References 37 publications
19
187
4
6
Order By: Relevance
“…Many investigators have confirmed the presence of the gap effect for SRT (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Some have proposed that the gap paradigm reduces saccade latency and also facilitates the appearance of a very short latency population in the SRT distribution, the so-called express saccades (ES) (for a review, see Ref.…”
mentioning
confidence: 99%
“…Many investigators have confirmed the presence of the gap effect for SRT (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Some have proposed that the gap paradigm reduces saccade latency and also facilitates the appearance of a very short latency population in the SRT distribution, the so-called express saccades (ES) (for a review, see Ref.…”
mentioning
confidence: 99%
“…For example, in the studies by Bekkering, Pratt and co-workers, when pointing movements were used (to move a handle to the left or to the right) a reliable and significant GAP effect was obtained -24 to 50 ms (7,8). However, when the choice keypress was introduced, the magnitude of the GAP effect was considerably smaller -6.3 to 11 ms (7), or did not reach significance, as reported by Reuter-Lorenz et al (5). Nevertheless, to move a handle is a mutually exclusive movement, i.e., you cannot move it to both sides at the same time, while it is perfectly possible to press both left and right keys simultaneously.…”
Section: Discussionmentioning
confidence: 69%
“…On the basis of their data, both ReuterLorenz et al (5,6) and Kingstone and Klein (9) proposed the so-called "two-component model" to explain the GAP effect. According to these investigators, the reduction in motor responses observed in the GAP condition should have two components: i) a warning component which follows any warning event and is common to both saccadic and manual responses, and ii) a fixation offset component which is specific for saccades and is observed when the FP is turned off.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, after training, some subjects were able to reduce or even eliminate the later peaks, thus resulting in an unimodal distribution with a single peak around 100 ms (7) -absolute latency criterion. Other researchers (10)(11)(12)(13)(14) , however, though confirming the reduction on SRTs with the gap paradigm, do not support the idea of ESs. According to their interpretation, neither the bimodality nor the latency criterion are convincing enough to propose the existence of ESs.…”
Section: Introductionmentioning
confidence: 78%